Exploring microsatellite instability in patients with advanced hepatocellular carcinoma and its tumor microenvironment. Issue 11 (1st October 2021) - Mukai, Shohei; Kanzaki, Hiroaki; Ogasawara, Sadahisa; Ishino, Takamasa; Ogawa, Keita; Nakagawa, Miyuki; Fujiwara, Kisako; Unozawa, Hidemi; Iwanaga, Terunao; Sakuma, Takafumi; Fujita, Naoto; Koroki, Keisuke; et al.
Abstract: Background and Aim: Immune checkpoint inhibitors and their combination with other agents have recently been available in advanced hepatocellular carcinoma (HCC). Hence, a thorough understanding of the tumor microenvironment based on tumor samples is yet to be achieved. This study aimed to explore the tumor microenvironment in advanced HCC in terms of microsatellite instability‐high (MSI‐H) by using tumor samples from advanced HCC patients eligible for systemic therapy. Methods: MSI‐H was assessed by polymerase chain reaction, and the expression of mismatch repair proteins, PD‐L1, CD8, VEGF, and HLA‐class1 was evaluated by immunohistochemistry. Whole‐exome sequencing was performed for MSI‐H tumor samples. Results: Of 50 patients, one (2.0%) was confirmed with MSI‐H. In the MSI‐H advanced HCC tumor, a high tumor mutation burden, infiltration of CD8 + lymphocytes, and low expression of VEGF were identified. Although PD‐L1 expression was negative, there was shrinkage of tumor following pembrolizumab. However, another tumor nonresponsive to pembrolizumab was present simultaneously. Checking the Cancer Genome Atlas (TCGA) database, we found a similar case to this patient. The TCGA case had unique gene features of miR‐21 and miR‐155 overexpression and hypermethylation of the MSH2 gene. Conclusion: We identified a very small number of MSI‐H cases in HCC using one tumor biopsy sample for each patient with advanced HCC. In addition, epigenetic aberrations possibly lead to MSI‐H in HCC patients. Since different HCC clones might coexist in the liver, sampling from multiple tumors should be considered to clarify the true proportion of MSI‐H in HCC and to analyze tumor microenvironments. Abstract : We confirmed that microsatellite instability‐high (MSI‐H) in hepatocellular carcinoma (HCC) was an extraordinarily rare case by using tumor samples of advanced HCC patients that were eligible for systemic therapies. Since the existence of heterogeneity in tumor microenvironment of advanced HCC was also implied, sampling from multiple tumors should be considered for analyzing tumor microenvironment including MSI‐H in patients with HCC.